Enhanced polybenzimidazole ion solvated composite membrane as well as preparation and application thereof
By preparing the enhanced polybenzimidazole ion solvated composite film, combining inorganic oxide nanoparticles and separator support materials, the problem of low OH-conductivity of traditional separators is solved, and efficient hydrochloric acid production performance and low energy consumption are achieved.
Patent Information
- Application Number
- CN202411744695.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-01
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-12-01
AI Technical Summary
Among the existing alkaline electrolytic water technology, the traditional separator has low OH-conductivity, which leads to low hydrogen production efficiency and high energy consumption. It is necessary to develop an exchange membrane with high OH-conductivity to improve the hydrogen production efficiency of electrolytic water and reduce energy consumption.
The enhanced polybenzimidazole ion solvated composite film is prepared by using the method of preparing the enhanced polybenzimidazole ion solvated composite film. The polybenzimidazole solution is formed by polycondensation reaction in polyphosphoric acid, and inorganic oxide nanoparticles are added, combined with the spacer support material to prepare the enhanced polybenzimidazole ion solvated composite film to improve the hydrophilicity and conductivity of the film.
Operate continuously in a high-concentration alkali environment for a long time and stable operation, reduce the membrane surface resistance to 0.035Ω·cm2, the current density can reach more than 8000mA·cm-2, the conductivity can reach up to 884mS·cm-1, the cold start response speed is fast, and the ohmic resistance of the electrolytic cell is low.
Smart Images

Figure BDA0005163403460000021 
Figure BDA0005163403460000022 
Figure BDA0005163403460000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogen production diaphragms and polymer functional membranes by electrolysis of water, and specifically relates to an enhanced polybenzimidazole ion solvation composite membrane and the preparation and application thereof. Background Art
[0002] Alkaline water electrolysis technology is one of the most mature and cost-effective solutions in the field of hydrogen production by water electrolysis. The technology has completed the industrialization process in the mid-20th century. Its notable features are the use of liquid electrolyte (KOH or NaOH aqueous solution) and porous separator (asbestos mesh or polyphenylene sulfide (PPS) mesh). The traditional separator has low OH- conductivity, resulting in low efficiency and high energy consumption of hydrogen production by water electrolysis. Therefore, a high OH-conductivity separator is designed. - Conductivity exchange membrane is the focus and hot spot in the development process of hydrogen production by water electrolysis.
[0003] The latest generation of diaphragms has excellent performance in terms of gas barrier, high temperature resistance, stability to concentrated alkali, etc., and has low resistance, so it has low energy consumption. Taking Agfa's Zirfon product as an example, the surface coating slurry contains zirconium dioxide and polymer, among which inorganic oxide nanoparticles such as zirconium dioxide are the main substances to improve its hydrophilicity, improve the compatibility of the diaphragm with the electrolyte, and reduce the internal resistance of the electrolytic cell. At the same time, due to the direct interaction between the surface slurry and PPS, the composite diaphragm usually exhibits higher physical stability than the PPS substrate.
[0004] Compared with porous composite membranes, ionic solvent membrane (ISM) is a dense homogeneous polymer membrane that can absorb a large amount of KOH electrolyte to form a homogeneous polymer / water / KOH electrolyte three-phase system. There are no fixed ionic groups in the structure of ISM, but ionic conductivity is obtained by absorbing liquid electrolytes. At present, polybenzimidazole (PBI) polymer is a commonly used ionic solvent membrane material in alkaline water electrolysis systems. When PBI is used in alkaline water electrolysis to produce hydrogen, PBI will react with KOH or NaOH in the electrolyte, absorb a large amount of alkali solution, and obtain a polybenzimidazole membrane material that can transfer hydroxide ions, thereby reducing membrane resistance. Summary of the invention
[0005] The object of the present invention is to provide a high conductivity, low membrane surface resistance enhanced polybenzimidazole ion solvation composite membrane for electrolysis of water to produce hydrogen and a preparation method and application thereof.
[0006] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0007] In a first aspect, the present invention provides a method for preparing an enhanced polybenzimidazole ion solvation composite membrane, comprising the following steps:
[0008] (1) in polyphosphoric acid, at least one of the aromatic tetraamine monomers represented by formula I and at least one of the dicarboxylic acid monomers represented by formula II are subjected to condensation polymerization, wherein the molar ratio of the aromatic tetraamine monomer to the dicarboxylic acid monomer is 1:1, and the reaction is performed until a viscous polybenzimidazole solution is obtained, and inorganic oxide nanoparticles dispersed in a phosphoric acid solution are added, wherein the ratio of the mass of the inorganic oxide nanoparticles to the total mass of the aromatic tetraamine monomer and the dicarboxylic acid monomer is 0.1-1:1-2, and after uniform stirring and degassing, a casting solution is obtained;
[0009]
[0010] In Formula I, -R- is a chemical single bond (i.e., Formula I is a biphenyl structure), -CH 2 -O-, -O-, or -CO-;
[0011] In formula II, A is selected from one of the chemical structures shown in ① to ⑨:
[0012]
[0013] Where 2≤n≤18;
[0014] (2) directly pouring the casting liquid obtained in step (1) onto a glass plate, scraping the film with an applicator, then spreading a mesh as a supporting material on the film, pouring the casting liquid into the glass plate, scraping the film with an applicator, and then cooling to room temperature at a certain relative humidity for hydrolysis to obtain a gel composite film; soaking the gel composite film in a carbonate aqueous solution, then soaking it in water to remove residual phosphoric acid in the film, and then soaking it in an alkaline solution to obtain an enhanced polybenzimidazole ion solvated composite film.
[0015] Preferably, the total concentration of all monomers in polyphosphoric acid is 5-50 mmol / 100 g.
[0016] Preferably, the polycondensation reaction is carried out according to the following steps: preheat the polyphosphoric acid and pour it into a three-necked flask; 2 Stir and heat at 100-160°C for 1-2h under protection; slowly add the aromatic tetraamine monomer and the dicarboxylic acid monomer to the polyphosphoric acid, and after complete dissolution, heat to 140-220°C for polycondensation reaction for 10-48h to obtain a polycondensation reaction liquid; then disperse the inorganic oxide nanoparticles in the phosphoric acid solution, add to the polycondensation reaction liquid and continue stirring for 0.5-2h, and obtain the casting liquid after degassing. The polycondensation reaction conditions are further preferred as follows: react at 140°C for 4h, heat to 160°C for 4h, and finally raise the reaction temperature to 190°C and maintain for 20h. In the above-mentioned staged polymerization process, in order to make the reaction of each stage as sufficient as possible, the molar amounts of the aromatic tetraamine monomer and the dicarboxylic acid monomer are matched as much as possible.
[0017] Preferably, the inorganic oxide nanoparticles are ZrO 2 、SiO 2 、TiO 2 One of them.
[0018] The ratio of the mass of the inorganic oxide nanoparticles to the total mass of the aromatic tetraamine monomer and the dicarboxylic acid monomer is 0.1-0.7:1, most preferably 0.1:1.
[0019] Preferably, the material of the separator is selected from one of polyphenylene sulfide (PPS), polypropylene (PP), polyethylene (PE), and polyester. In a specific embodiment of the present invention, the separator is a hydrophilically modified PPS separator.
[0020] Preferably, in step (2), the composite membrane has a thickness of 60-600 μm and the separator has a thickness of 50-400 μm.
[0021] Preferably, in step (2), after scraping the film, the film is cooled to room temperature at a relative humidity of 30-100% and hydrolyzed for 4-24 hours.
[0022] Preferably, in step (2), the alkaline solution is a KOH aqueous solution or a NaOH aqueous solution.
[0023] Preferably, in step (2), the carbonate is potassium carbonate or sodium carbonate.
[0024] Preferably, in step (2), the gel composite membrane is placed in K 2 CO 3 Or Na 2 CO 3 The membrane was immersed in an aqueous solution for 24 hours, and then immersed in water for 24 hours to remove the residual phosphoric acid in the membrane, and then immersed in an alkaline solution for 48 hours to obtain an enhanced polybenzimidazole ion solvation composite membrane.
[0025] In a second aspect, the present invention provides a reinforced polybenzimidazole ion solvation composite membrane prepared according to the preparation method described in the first aspect.
[0026] In a third aspect, the present invention provides the use of the enhanced polybenzimidazole ion solvation composite membrane described in the second aspect in alkaline electrolysis of water.
[0027] Compared with the prior art, the beneficial effect of the present invention is that the present invention combines the advantages of ion-solvated PBI membrane and the new generation Zirfon membrane to prepare an enhanced sol-gel mesh-enhanced polybenzimidazole-inorganic oxide composite membrane. The composite membrane can operate stably for a long time in a high-concentration alkaline environment and effectively reduces the membrane surface resistance to a minimum of 0.035Ω·cm 2, which is much smaller than the Zirfon series diaphragms; and the membrane prepared by the present invention has a current density of up to 8000 mA cm at 80°C, 6 M KOH, and a cell voltage of 2.0 V. -2 above. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 The IV curves of the membrane prepared in Example 1 in KOH solutions of different concentrations at 80°C are shown in Figure 1. In 6M KOH, the current densities at 1.8V and 2V are 4669 and 8167 mA·cm, respectively. -2 , in 2M KOH, the current density is 3895 mA cm -2 , and has excellent electrochemical performance in low concentration alkaline solution.
[0029] Figure 2 The IV curves of the membrane prepared in Example 1 at different temperatures in 6M KOH solution show that even at a low temperature of 40°C, the current density at 1.8V and 2V is 1994 and 3918mA·cm respectively. -2 , cold start response speed is fast.
[0030] Figure 3 The AC impedance diagram of the membrane prepared in Example 1 at different current densities in 6M KOH solution at 80°C, the ohmic resistance of the electrolytic cell is as low as 0.035Ω·cm 2 .
[0031] Figure 4 The conductivity curve of the membrane prepared in Example 1-4 at 80°C and 6M KOH solution shows that the highest conductivity is 884 mS·cm -1 As the content of zirconia nanoparticles increases, the conductivity remains at 700 mS·cm -1 above.
[0032] Figure 5 The dried PBI / PPS / ZrO prepared in Example 4 2 Surface morphology of the gel film, showing that the nano-zirconia nanoparticles are evenly dispersed.
[0033] Figure 6 The dried PBI / PPS / ZrO prepared in Example 4 2 The cross-sectional morphology of the gel film shows that the film has a layered structure, which can increase the absorption of alkaline solution. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clear, the technical solution will be clearly and completely described below through embodiments, but the protection scope of the present invention is not limited thereto.
[0035] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0036] Embodiment 1:
[0037] Preheat polyphosphoric acid (100 g) and pour into a 250 mL three-necked flask. 2 Stir and heat at 140℃ for 2h under protection. Slowly add 3,3'-diaminobenzidine (2.14g, 10mmol) and terephthalic acid (1.66g, 10mmol) to polyphosphoric acid, react at 140℃ for 4h, heat to 160℃ for 4h, and finally raise the reaction temperature to 190℃ and keep it for 20h. 2 Nanoparticles (0.38 g) were dispersed in 10 mL of 85 wt % phosphoric acid solution, added to the reaction solution and stirred for 1 h to obtain a casting solution, which was then degassed by vacuum low-speed stirring.
[0038] Soak a 100μm PPS mesh in concentrated sulfuric acid at room temperature for 10 hours for hydrophilic modification, then wash and dry for later use. Prepare a clean glass plate and place it on a heating plate (60°C), pour the casting liquid directly onto the glass plate, and use a 350μm applicator to scrape the film. Spread the hydrophilically modified PPS mesh on the membrane as a supporting material. After staying for three minutes, pour some casting liquid and use a 450μm scraper to scrape another layer on the mesh. Cool to room temperature at 50% relative humidity for hydrolysis for 8 hours to obtain a gel composite membrane. Finally, place the membrane at 10% K 2 CO 3 The membranes were immersed in an aqueous solution for 24 h, then immersed in water for another 24 h to remove the residual PA in the membranes, and then immersed in a 6 M KOH solution for 48 h.
[0039] Embodiment 2:
[0040] Preheat polyphosphoric acid (100 g) and pour into a 250 mL three-necked flask. 2 Stir and heat at 140℃ for 2h under protection. Slowly add 3,3'-diaminobenzidine (2.14g, 10mmol) and isophthalic acid (1.66g, 10mmol) to polyphosphoric acid, react at 140℃ for 4h, heat to 160℃ for 4h, and finally raise the reaction temperature to 190℃ and keep it for 20h. 2 Nanoparticles (0.76 g) were dispersed in 10 mL of 85 wt % phosphoric acid solution, added to the reaction solution and stirred for 1 h to obtain a casting solution, which was then degassed by low-speed stirring under vacuum.
[0041] Soak a 100μm PPS mesh in concentrated sulfuric acid at room temperature for 10 hours for hydrophilic modification, then wash and dry for later use. Prepare a clean glass plate and place it on a heating plate (60°C), pour the casting liquid directly onto the glass plate, and use a 350μm applicator to scrape the film. Spread the hydrophilically modified PPS mesh on the membrane as a supporting material. After staying for three minutes, pour some casting liquid and use a 450μm scraper to scrape another layer on the mesh. Cool to room temperature at 50% relative humidity for hydrolysis for 8 hours to obtain a gel composite membrane. Finally, place the membrane at 10% K 2 CO 3 The membranes were immersed in an aqueous solution for 24 h, then immersed in water for another 24 h to remove the residual PA in the membranes, and then immersed in a 6 M KOH solution for 48 h.
[0042] Embodiment 3:
[0043] Preheat polyphosphoric acid (100 g) and pour into a 250 mL three-necked flask. 2 Stir and heat at 140℃ for 2h under protection. Slowly add 3,3'-diaminobenzidine (2.14g, 10mmol) and terephthalic acid (1.66g, 10mmol) to polyphosphoric acid, react at 140℃ for 4h, heat to 160℃ for 4h, and finally raise the reaction temperature to 190℃ and keep it for 20h. 2 Nanoparticles (1.52 g) were dispersed in 10 mL of 85 wt % phosphoric acid solution, added to the reaction solution and stirred for 1 h to obtain a casting solution, which was then degassed by vacuum stirring at a low speed.
[0044] Soak a 100μm PPS mesh in concentrated sulfuric acid at room temperature for 10 hours for hydrophilic modification, then wash and dry for later use. Prepare a clean glass plate and place it on a heating plate (60°C), pour the casting liquid directly onto the glass plate, and use a 250μm applicator to scrape the film. Spread the hydrophilically modified PPS mesh on the membrane as a supporting material. After staying for three minutes, pour some casting liquid and use a 350μm scraper to scrape another layer on the mesh. Cool to room temperature at 50% relative humidity for hydrolysis for 8 hours to obtain a gel composite membrane. Finally, place the membrane in 10% K 2 CO 3 The membranes were immersed in an aqueous solution for 24 h, then immersed in water for another 24 h to remove the residual PA in the membranes, and then immersed in a 6 M KOH solution for 48 h.
[0045] Embodiment 4:
[0046] Preheat polyphosphoric acid (100 g) and pour into a 250 mL three-necked flask. 2Stir and heat at 140℃ for 2h under protection. Slowly add 3,3'-diaminobenzidine (2.14g, 10mmol) and terephthalic acid (1.66g, 10mmol) to polyphosphoric acid, react at 140℃ for 4h, heat to 160℃ for 4h, and finally raise the reaction temperature to 190℃ and keep it for 20h. 2 Nanoparticles (2.66 g) were dispersed in 10 mL of 85 wt % phosphoric acid solution, added to the reaction and stirred for 1 h to obtain a casting solution, which was then degassed by vacuum stirring at a low speed.
[0047] Soak a 100μm PPS mesh in concentrated sulfuric acid at room temperature for 10 hours for hydrophilic modification, then wash and dry for later use. Prepare a clean glass plate and place it on a heating plate (60°C), pour the casting liquid directly onto the glass plate, and use a 250μm applicator to scrape the film. Spread the hydrophilically modified PPS mesh on the membrane as a supporting material. After staying for three minutes, pour some casting liquid and use a 450μm scraper to scrape another layer on the mesh. Cool to room temperature at 50% relative humidity for hydrolysis for 8 hours to obtain a gel composite membrane. Finally, place the membrane at 10% K 2 CO 3 The membrane was immersed in an aqueous solution for 24 hours, then immersed in water for another 24 hours to remove the residual PA in the membrane, and then immersed in a 6M KOH solution for 48 hours. The obtained membrane was immersed in deionized water and fully washed until neutral, and then dried. The surface morphology and cross-sectional morphology of the obtained membrane are shown in Figure 2. Figure 5 and Figure 6 shown.
[0048] The performance of the membranes prepared in Examples 1-4 was tested:
[0049] IV curve test: Use a constant temperature zero gap alkaline electrolysis cell to test the membrane for hydrogen production by alkaline electrolysis of water. The cathode uses 0.5 mg / cm 2 The gas diffusion electrode loaded with platinum (provided by Suzhou Shengernuo) was used as the anode. The self-made NiFe-LDH was used for the NiFe-LDH. 0.350 g Ni(NO3) 2 6H 2 O, 0.162g Fe(NO3) 3 9H 2O and 0.32g urea were dissolved in 30ml deionized water and stirred vigorously, and then the pre-washed nickel foam (2×2cm) was immersed in the solution and reacted at 120°C for 12h in a Teflon-lined autoclave. Wash with deionized water and dry in a vacuum oven at 25°C for 12h to obtain NiFe-LDH. Electrolysis experiments were carried out under different hydrogen production conditions. The membrane sample was placed between the anode and the cathode, and the current density was measured in the voltage range of 1.3-2.0V to generate a polarization curve. The IV curves of the membrane prepared in Example 1 in KOH solutions of different concentrations at 80°C are shown in Figure 2. Figure 1 As shown, the IV curves of the membrane prepared in Example 1 at different temperatures in 6M KOH solution are as follows Figure 2 shown.
[0050] Constant current AC impedance: The AC impedance of the in-situ electrolyzer was tested at different current densities in a 6M KOH solution at 80°C, with a frequency sweep range of 0.1Hz to 100kHz. The AC impedance diagram of the membrane electrode prepared in Example 1 at different current densities in a 6M KOH solution at 80°C is shown in Figure 3 .
[0051] Conductivity test: Place the membrane in a 6M KOH solution and soak until saturated, cut the dry membrane into strips of 1cm×4cm, place between parallel platinum wires, connect to an electrochemical workstation, and use the AC impedance method to measure the impedance of the membrane. The frequency scanning range is 1Hz~100kHz; the test temperature range is 20~80℃, and the conductivity calculation formula is:
[0052]
[0053] Where, σ is the conductivity of the membrane (S / cm); R is the impedance of the membrane (Q); l is the distance between the two electrodes (cm); A is the effective cross-sectional area of the membrane (cm 2 ).
[0054] The conductivity curve of the membrane prepared in Example 1-4 at 80°C and 6M KOH solution is shown in Figure 4 .
Claims
1. A method for preparing an enhanced polybenzimidazole ion solvated composite membrane, characterized in that: The preparation method comprises the following steps: (1) in polyphosphoric acid, at least one of the aromatic tetraamine monomers represented by formula I and at least one of the dicarboxylic acid monomers represented by formula II are subjected to condensation polymerization, wherein the molar ratio of the aromatic tetraamine monomer to the dicarboxylic acid monomer is 1:1, and the reaction is performed until a viscous polybenzimidazole solution is obtained, and inorganic oxide nanoparticles dispersed in a phosphoric acid solution are added, wherein the ratio of the mass of the inorganic oxide nanoparticles to the total mass of the aromatic tetraamine monomer and the dicarboxylic acid monomer is 0.1-1:1-2, and after uniform stirring and degassing, a casting solution is obtained; In formula I, -R- is a chemical single bond, -CH2-O-, -O- or -CO-; In formula II, A is selected from one of the chemical structures shown in ① to ⑨: Where 2≤n≤18; (2) directly pouring the casting liquid obtained in step (1) onto a glass plate, scraping the film with an applicator, then spreading a mesh as a supporting material on the film, pouring the casting liquid into the glass plate, scraping the film with an applicator, and then cooling to room temperature at a certain relative humidity for hydrolysis to obtain a gel composite film; soaking the gel composite film in a carbonate aqueous solution, then soaking it in water to remove residual phosphoric acid in the film, and then soaking it in an alkaline solution to obtain an enhanced polybenzimidazole ion solvated composite film.
2. The preparation method according to claim 1, characterized in that: The total concentration of all aromatic tetraamine monomers and dicarboxylic acid monomers in polyphosphoric acid is 5-50 mmol / 100 g.
3. The preparation method according to claim 1, characterized in that: The polycondensation reaction is carried out according to the following steps: preheating polyphosphoric acid and pouring it into a three-necked flask, stirring and heating at 100-160° C. for 1-2 hours under the protection of dry N2; slowly adding aromatic tetraamine monomer and dicarboxylic acid monomer into polyphosphoric acid, and after complete dissolution, heating to 140-220° C. for polycondensation reaction for 10-48 hours to obtain a polycondensation reaction liquid; then dispersing inorganic oxide nanoparticles in phosphoric acid solution, adding the inorganic oxide nanoparticles into the polycondensation reaction liquid and continuing to stir for 0.5-2 hours, and obtaining a casting liquid after degassing.
4. The preparation method according to claim 1, characterized in that: The inorganic oxide nanoparticles are one of ZrO2, SiO2 and TiO2.
5. The preparation method according to claim 1, characterized in that: The ratio of the mass of the inorganic oxide nanoparticles to the total mass of the aromatic tetraamine monomer and the dicarboxylic acid monomer is 0.1-0.7:
1.
6. The preparation method according to claim 1, characterized in that: The material of the separator is selected from one of polyphenylene sulfide, polypropylene, polyethylene and polyester.
7. The preparation method according to claim 1, characterized in that: In step (2), after scraping the film, the film is cooled to room temperature at a relative humidity of 30-100% and hydrolyzed for 4-24 hours.
8. The preparation method according to claim 1, characterized in that: In step (2), the alkaline solution is a KOH aqueous solution or a NaOH aqueous solution.
9. A reinforced polybenzimidazole ion solvated composite membrane prepared according to the preparation method according to any one of claims 1 to 8.
10. Use of the enhanced polybenzimidazole ion solvation composite membrane as claimed in claim 9 in alkaline electrolysis of water.
Citation Information
Patent Citations
Electrochemical apparatus isolation membrane and preparation method therefor
CN107732108A
Polymer composite film, preparation method thereof and lithium ion battery comprising same
CN108242522A
Nanometer composite membrane for flow battery and preparation method of nanometer composite membrane
CN115548362A
Preparation method of polybenzimidazole high-temperature proton exchange membrane
CN115692805A
Inorganic doped composite porous polymer diaphragm with high hydrophilicity, preparation method and application
CN115895014A